TINJAUAN PENDIDIKAN DALAM PERSPEKTIF ISLAM - Mubarok, Said (STAI Hubbulwathan Duri, 2015)
The Qur'an mentions education with some terms, among others tarbiyah, study groups and ta'dib ,. Tarbiyah word implies education, said ta'dib implies refinement of character, and said ta'lim implies the teaching of science. However, the third word is essentially an integrated whole, meaning that if education is attributed to ta'dib he must go through study groups. While understanding tarbiyah contains a tendency to grow and develop in dinamis.tujuan end of Islamic education is a private establishment kholifah for students who have the character, the spirit in the body, the will which is free, and resourceful. In other words, the task of education is to develop the fourth aspect of the human being so that he can occupy the position as kholifah. So also in formulating the general and specific objectives, should be in accordance with the final destination of a private establishment kholifah. Personal kholifah is basically a well-rounded individual who has a balance of all its potential. To then functioned appropriately in accordance with the tasks entrusted to him by Allah. In the whole person there is independence so important in directing behavior to lead to success in living vagaries of life in the world.